Discipline Analysis Of Work, Motivation And Loyalty Towards Employee Performance (Case Study At Gorontalo State University) - Musa, Fandy Nugroho Hardiknasiono; Tumbel, Altje; Wullur, Magdalena (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2021)
This study aims to partially determine the positive and significant influence of work discipline, motivation and loyalty on employee performance at Gorontalo State University. The population in this study is the State Civil Apparatus at Gorontalo State University, amounting to 247 people. The data collection method uses a questionnaire that is by collecting data through a list of questions and distributing questionnaires to employees at Gorontalo State University. The research results obtained that there is a significant influence by work discipline on employee performance in the Gorontalo State University environment. The better the application of work discipline on employees will also improve employee performance. There is a significant influence by work motivation on employee performance in the State University of Gorontalo. The high level of motivation possessed by employees is one of the keys in improving employee performance. So the existence of programs that are motivating work must be intensified even more. There is a significant influence by loyalty on the performance of employees in the environment of Gorontalo State University. Employee loyalty is the reason why labor turn over is so low. This was also triggered by the university's commitment to opening opportunities for its employees including honorary employees in achieving good career paths. There is a significant influence by work discipline, motivation, and loyalty simultaneously on employee performance in Gorontalo State University. This indicates that work discipline alone is not enough to stimulate employee performance. The implementation of preventive policies to direct employee behavior to be disciplined must also be supported by the existence of programs that can motivate employee work. That way employee loyalty can also be created and enhanced. Synergy between the three variables will have a positive impact on improving employee performance so that it will also affect the overall university performance as an outcome of employee performance. All of these factors are needed considering the vision of the university as a leading university in the Southeast Asian region which certainly requires strong support and commitment as well as good performance from all elements in Gorontalo State University.